2018
DOI: 10.29252/beat-060105
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Morphine and Low Dose Ketamine for Pain Control of Patients with Long Bone Fractures: A Randomized, Double-Blind, Clinical Trial

Abstract: Objective:To compare the effects of intravenous morphine and a low dose of ketamine on pain intensity of patients with traumatic fractures of the long bones. Methods: This randomized, controlled, double-blinded, clinical trial was conducted in the adult emergency department (ED) of Emam Khomeini hospital, a tertiary general hospital affiliated with Mazandaran University of Medical Sciences, in Northern Iran, during a 6-month period. Patients were randomly assigned to receive intravenous morphine (0.1 mg/kg) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“… 12–14,20,21,23 The pooled estimate showed no significant difference in mean pain scores between LDK and morphine within 15 minutes (MD = −0.15, 95% CI = −0.68 to 0.38). Six studies reported a pain score between 15 and 30 minutes 13,14,20–23 . The pooled estimate showed no significant difference in mean pain scores between groups (MD = −0.03, 95% CI = −0.37 to 0.32).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“… 12–14,20,21,23 The pooled estimate showed no significant difference in mean pain scores between LDK and morphine within 15 minutes (MD = −0.15, 95% CI = −0.68 to 0.38). Six studies reported a pain score between 15 and 30 minutes 13,14,20–23 . The pooled estimate showed no significant difference in mean pain scores between groups (MD = −0.03, 95% CI = −0.37 to 0.32).…”
Section: Resultsmentioning
confidence: 93%
“…Three studies with a total of 306 patients (153 in the LDK group and 153 in the morphine group) reported on the use of rescue medication (Figure 4). 13,20,22 The pooled estimate showed no significant difference in need for rescue medication between LDK and morphine (14.4% vs. 11.1%; RR = 1.26; 95% CI: 0.50 to 3.16, very low certainty). Seven of the included studies with a total of 1,065 patients (535 in the LDK group and 530 in the morphine group) reported on nausea 13,14,20‐24 .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Results in regard to frequency of adverse events and efficacy at later points were mixed. [8][9][10] This study suggests that low-dose intravenous ketamine provides analgesia comparable to that of intravenous morphine at 0.1 mg/kg. 11 However, it is unclear how ketamine compares with titrated opioids or whether it can be effectively redosed or titrated.…”
Section: Commentarymentioning
confidence: 84%